Improving Students Proficiency In English. - Pawanchik, Shahrier (Universiti Sains Malaysia, 2006)
The Mmistry of Education in Malaysia introduced the Malaysian University English Tests (MUET) in 2000 with the Objective of consolidating and enhancing the English language ability of the pre-university(upper secondary and matriculation) students so that at the tertiary level these students are able to commumcate with ease in the language.